2020
DOI: 10.1097/mcg.0000000000001192
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences Among Patients Hospitalized With Cirrhosis in the United States

Abstract: Background & Aims: Gender disparities exist in outcomes among patients with cirrhosis. We sought to evaluate the role of gender on hospital course and in-hospital outcomes in patients with cirrhosis to help better understand these disparities. Study:We analyzed data from the National Inpatient Sample (NIS), years 2009-2013, to identify patients with any diagnosis of cirrhosis. We calculated demographic and clinical characteristics by gender, as well as cirrhosis complications. Our primary outcome was inpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 45 publications
(49 reference statements)
1
24
1
Order By: Relevance
“…Since we utilized a large population cohort, our findings most closely compare to other large population based studies. A recent study using the National Inpatient Sample noted a decrease in all-cause mortality among women in hospitalized patients with cirrhosis (aOR 0.86, p<0.001), a remarkably comparable effect size to our study [6]. Similarly, a population based cohort of patients with cirrhosis in the United Kingdom found that female sex had a significant protective association against all-cause mortality (aHR for females 0.84, 95% CI (0.77, 0.91)) [10].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Since we utilized a large population cohort, our findings most closely compare to other large population based studies. A recent study using the National Inpatient Sample noted a decrease in all-cause mortality among women in hospitalized patients with cirrhosis (aOR 0.86, p<0.001), a remarkably comparable effect size to our study [6]. Similarly, a population based cohort of patients with cirrhosis in the United Kingdom found that female sex had a significant protective association against all-cause mortality (aHR for females 0.84, 95% CI (0.77, 0.91)) [10].…”
Section: Discussionsupporting
confidence: 85%
“…Despite its importance, the relationship between patient sex and outcomes of patients with cirrhosis remains unclear. A recent study in a large sample of hospitalized patients with cirrhosis found that women were 14% less likely to die while hospitalized [6]. This analysis was limited in that it could not track outcomes post discharge and patient sex itself has been associated with admission to the hospital, potentially introducing selection bias [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies indicating a gender effect report improved survival in women [1]. A recent study based on approximately 553 000 patients hospitalized with cirrhosis found in-hospital-mortality to be reduced by fourteen percent in females as compared to males [4]. It is not known, however, whether a positive effect of female sex is true for all cirrhotic patients, or whether it is restricted to decompensated patients.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, UTI represents a disproportionate percentage of infections in women compared with men, and women have higher inpatient overall survival than men in patients with cirrhosis. 30 However, UTI appears to have among the highest rates of multidrug-resistant organisms of other bacterial infections, 31 and can still be associated with a twofold increase in 90-day mortality. 32 As multidrug-resistant infections are becoming more prevalent and have worse outcomes, UTI mortality may be expected to rise in the future.…”
Section: Discussionmentioning
confidence: 99%